Influence of LKPD to Facilitate Cooperative Group Investigation in Improving Students' Science Process Skills - Suliwa; Wahono Widodo; Munasir (Indonesia Approach Education, 2021)
This study purpose to know the effect of LKPD to facilitate group investigation cooperatives in improving students' science process skills in learning science material for object motion in class VIII MTs Al Miftah Modung for the 2020/2021 academic year. This research is experimental research using a Quasi-Experimental research design. The sample used was all students of class VIII as many as 20 students. The analysis technique of hypothesis testing students' science process skills using Free sample t-test with SPSS version 20.00 program. The results of hypothesis testing students' science process skills were obtained score –ttable ≤ tcount ≥ ttable (-2.262 ️ ≤ 5.071 ≥️ 2,262) then Ho is rejected and Ha is accepted. The average percentage of implementation is 90.25% with a very good category. the average student response questionnaire is 94% with a very good category. Based on the results of the data analysis, it can be concluded that there is an influence of LKPD to facilitate group investigation in improving science process skills for students.